2018
DOI: 10.1007/s11356-018-1753-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of economic growth, nonrenewable and renewable energy consumption, and urbanization on carbon emissions in Sub-Saharan Africa

Abstract: The present study explores the impact of economic growth; urban expansion; and consumption of fossil fuels, solid fuels, and renewable energy on environmental degradation in developing economies of Sub-Saharan Africa. To demonstrate its findings in detail, the study adopts a system generalized method of moment (GMM) on a panel of 34 emerging economies for the period from 1995 to 2015. The results describe that the consumption of fossil and solid fuels for cooking and expansion of urban areas are significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
85
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(133 citation statements)
references
References 51 publications
16
85
0
3
Order By: Relevance
“…Large cities in Sub-Saharan Africa, like KCP, Capital of Democratic Republic of Congo (DRC), are facing a dramatic population explosion (Khennas 2012;Hanif 2018;Mambanzulua et al 2015a). This is the result of the increasing of rural-urban migration and the displacement of people from areas of armed con icts such as the Eastern part of the DRC.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Large cities in Sub-Saharan Africa, like KCP, Capital of Democratic Republic of Congo (DRC), are facing a dramatic population explosion (Khennas 2012;Hanif 2018;Mambanzulua et al 2015a). This is the result of the increasing of rural-urban migration and the displacement of people from areas of armed con icts such as the Eastern part of the DRC.…”
Section: Introductionmentioning
confidence: 99%
“…This is the result of the increasing of rural-urban migration and the displacement of people from areas of armed con icts such as the Eastern part of the DRC. Those displacements cause anarchic subdivisions in the peri-urban green spaces and increase crops and energy consumption in KCP (Hanif 2018;Mambanzulua et al 2015a, b). Therefore, in KCP there is an increase in the production of improperly managed wastes, deforestation and decreasing areas of arable lands which are otherwise infertile (Hanif 2018;Mambanzulua et al 2015aMambanzulua et al , 2015b; Barrios et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More researchers [7,12] reported that carbon emissions have affected health globally. According to Ref.…”
Section: Introduction mentioning
confidence: 99%